A Critical Review on Millets (Superfood of all Time): Importance, Challenges and Opportunities - Sharandeep Singh Cheema; Vijay Kumar; Anshu; Aditya; V.D. Ebenezer (Archives of Current Research International, 2024)
Climate change, water scarcity, population growth, rising food prices, and other socioeconomic repercussions are anticipated to pose a serious danger to agriculture and global food security in the twenty-first century, especially for the world’s poorest residents of arid and subarid countries. We must concentrate on dry lands in order to significantly boost the production of grains because agricultural fields with irrigation systems have been fully utilized. It is difficult to use arid areas to produce sufficient quality grains because of their poor productivity. The most important source of food in the world is cereal grains, which also play an important part in the global diet of people. In the semiarid tropics of Africa and Asia, millet is one of the most significant drought-resistant crops and is a major source of carbohydrates and proteins for the local population. Additionally, millet grain is currently attracting more interest from food scientists, technologists, and nutritionists due to its significant contribution to national food security and potential health advantages. The phytochemicals found in millet grains have a beneficial impact on human health by reducing phytates and cholesterol levels. The quest for substitute grains is necessary to relieve the pressure caused by the frenetic demands on cereals and their uses in numerous industries. The performance improved when pearl and finger millets were substituted for maize in the diets of several animals. In terms of poor growth conditions and high nutritional value, millets outperform other grains like wheat and rice as crops that are climate change compliant. These strategies will aid in the fight against hunger and malnutrition while also providing monetary benefits to the millet growers and other stakeholders.